Behavior of the Use of Personal Protective Equipment for Forest and Land Fires on the Quick Response Team Officers at Badan Penanggulangan Bencana Daerah, Bengkalis Regency, 2022 - Diah Tantri Kusumaningtiyas; Endang Purnawati Rahayu; Oktavia Dewi (Budapest International Research and Critics University, 2022)
The purpose of this research is to find out behavior of the use of personal protective equipment for forest and land fires on the Quick Response Team Officers at Badan Penanggulangan Bencana Daerah, Bengkalis Regency in 2022. This study uses a qualitative research design with a phenomenological approach. Data collection methods use are interviews, observation, and documentation. The technique uses in determining the informants is using a purposive sampling technique. The data processing technique used in this study is a triangulation technique. The results show that the behavior of using personal protective equipment for forest and land fires at the Bengkalis Regency Regional Disaster Management Agency's Quick Response Team in 2022 had not been carried out optimally.